RELIGIOUS COURTS IN MUSLIM COUNTRIES: THE GRIP OF THE WESTERN LEGAL SYSTEM ON THE TRANSFORMATION OF THE KUWAITI JUDICIARY - Layla, Desteny; Asasriwarni, Asasriwarni; Zulfan, Zulfan; Taufiq, Arif (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
AbstractThis research aims to examine the existing justice system in one of the Muslim countries in the world, namely Kuwait, which has undergone transformation due to the influence of the western legal system. This research is library research, namely research carried out by examining various related research and literature. The data source in this research is secondary data. The results of this research are that the grip of the Western legal system has changed the structure of the legal system in Kuwait. This can be seen in the legal system in Kuwait which has undergone a transformation, initially only influenced by Islam but currently also influenced by foreign legal systems, such as France, England and Egypt. This is due to the background of the Kuwaiti state which was once under the supervision of a foreign country such as England. The legal system in Kuwait has currently undergone a transformation, in the form of a combination of British common law, French civil law, Egyptian civil law and Islamic law (Shariah) by implementing the Sharia Law for its civil law. This causes the courts in Kuwait to be divided into three levels: the Court of First Instance, the Court of Appeal and the Court of Cassation. Within each of the three levels of courts, special boards or tribunals are created to adjudicate civil, criminal, commercial or financial, administrative, and personal status matters, and the courts may establish additional special councils or tribunals as necessary.